A permselective and multifunctional 3D N-doped carbon nanotubes interlayer for high-performance lithium-sulfur batteries. (20th July 2022) - Liu, Mingliang; Bai, Wuxin; Guo, Hui; Sun, Jingwen; Liu, Yongsheng; Fang, Mingkun; Guo, Tong; Yang, Shaolin; Vasiliev, Aleksandr L.; Kulesza, Pawel J.; Hu, Yanling; Ouyang, Xiaoping; et al.
Abstract: Here in-situ Raman indicates that the shuttle effect induced by polysulfides occurs during the whole discharge and charge process in lithium-sulfur batteries (LSBs), leading to irreversible loss of sulfur and generation of lithium dendrites. To solve the above problems, we construct a N-doped carbon nanotubes/carbonized cellulose paper (IF-N-CNTs-CCP) with three-dimensional conductive network structure through noncovalent modification assisted high-temperature carbonization. IF-N-CNTs-CCP interlayer can effectively block the shuttle effect by strong chemisorption and physical barrier, improving the utilization of sulfur. However, it doesn't prevent the free migration of lithium ions, resulting in a remarkable acceleration of electrochemical reaction kinetics. Moreover, the three-dimensional IF-N-CNTs-CCP interlayer can provide a large number of lithiophilic sites and significantly reduce the regional current density, thus inhibiting the growth of lithium dendrites, enhancing the safety of LSBs. As a result, the LSBs with IF-N-CNTs-CCP interlayer deliver a negligible capacity fading rate of 0.037% per cycle after 500 cycles at 2.0 C, and a high-capacity retention of 95% at 0.2 C with a sulfur loading of 3 mg/cm 2 with a correspondingly lean electrolyte condition (E/S ratio = 6 µL/mg). This work provides an effective strategy for the application of functional interlayer in LSBs, which can suppress the shuttle effect and lithium dendrite. Graphical abstract: Image, graphical abstract